(Invited) Temperature Influence on Current Leakage and Hysteresis of Nc-CdSe Embedded Zr-Doped HfO2 High-k Dielectric Nonvolatile Memory. (31st March 2015) - Zhang, Shumao; Kuo, Yue
Abstract : Current leakage and hysteresis characteristics of a MOS capacitor containing nanocrystalline CdSe embedded ZrHfO high- k gate dielectric at different temperatures have been investigated. Variation of the temperature changes the supply and energy state of charges from the Si wafer, the charge trapping and retaining properties of the embedded nanocrystal, and the conductivity of the high- k stack. They are responsible for the magnitude and hysteresis of the leakage current. Depending on the polarity and magnitude of the applied voltage and the substrate temperature, charges are transferred following the Schottky emission, Poole-Frenkel, or Fowler-Nordheim mechanism. The leakage current hysteresis of the nanocrystalline CdSe embedded sample is smaller than that of the control sample, and the difference increases as the temperature rises. These phenomena are related to the defect density, the physical thickness, and the charge trapping mechanism.